The Five-Year Plan for Bombay State (1951-52 to 1955-56) Directorate of Publicity, Government of Bombay - Planning Commission (Planning Commission, 1952)
The Five-Year Plan, just adopted, marks the beginning of a new era in our economic and social history. The plan is an expression of a free and democratic people, who having attained political independence, are determined to chalk out a programme of rapid and orderly development for themselves so as to raise the general standard of living. Only a few years back, it was difficult to conceive of a single political and economic order for the country as a wholes We had to face certain immediate problems like the integration of States, the rehabilitation of displaced persons and the formulation of a stable constitution for the country.
Directorate of Publicity, Government of Bombay